2001
DOI: 10.1021/np0004193
|View full text |Cite
|
Sign up to set email alerts
|

Five New Insecticidal Sesquiterpenoids from Celastrus angulatus

Abstract: Five new sesquiterpene polyol esters were isolated from the root bark of Celastrus angulatus by bioassay-guided fractionation. Their structures were determined by spectral data interpretation as 1alpha,2alpha,6beta,8beta,13-pentaacetoxy-9beta-benzoyloxy-4beta-hydroxy-beta-dihydroagarofuran (1), 1alpha,2alpha,6beta-triacetoxy-8alpha-(beta-furancarbonyloxy)-9beta-benzoyloxy-13-isobutanoyloxy-4beta-hydroxy-beta-dihydroagarofuran (2), 1alpha,2alpha,6beta-triacetoxy-8beta-isobutanoyloxy-9beta-(beta-furancarbonyloxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
66
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 8 publications
0
66
0
Order By: Relevance
“…-Microtropis fokienensis Dunn (Celastraceae) is a small shrub that grows in high-altitude forests throughout southern China and Taiwan [1]. Various dihydroagarofuranoid sesquiterpenes [2] [3], sesquiterpene alkaloids [4], and triterpenes [5] [6] are widely distributed in plants of the family Celastraceae. Many of these compounds exhibit insecticidal [2], anti-inflammatory [3], anti-AIDS [5], and antitumor [5] [6] activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…-Microtropis fokienensis Dunn (Celastraceae) is a small shrub that grows in high-altitude forests throughout southern China and Taiwan [1]. Various dihydroagarofuranoid sesquiterpenes [2] [3], sesquiterpene alkaloids [4], and triterpenes [5] [6] are widely distributed in plants of the family Celastraceae. Many of these compounds exhibit insecticidal [2], anti-inflammatory [3], anti-AIDS [5], and antitumor [5] [6] activities.…”
mentioning
confidence: 99%
“…Various dihydroagarofuranoid sesquiterpenes [2] [3], sesquiterpene alkaloids [4], and triterpenes [5] [6] are widely distributed in plants of the family Celastraceae. Many of these compounds exhibit insecticidal [2], anti-inflammatory [3], anti-AIDS [5], and antitumor [5] [6] activities. In our continuing studies on the antitubercular constituents of Formosan plants, over 400 species have been screened so far for their in vitro antituberculosis activities, and M. fokienensis has been found to be one of the active species.…”
mentioning
confidence: 99%
“…90°. [8][9][10] From the NOESY spectrum of 1, the strong correlation between H-7/H-9 and H-9/H-13 indicated the presence of cis-orientation of H-9. Thus, compound 1 was identified as 1S,13-diacetyloxy-4S-hydroxy-6R-(3-)furancarbonyloxy-9S-cinnamoyloxy-b-dihydroagarofuran.…”
Section: Resultsmentioning
confidence: 99%
“…The cou- pling constant, J 8,9 ϭ6.0 Hz suggested that H-8 and H-9 have a different orientation. 9,10) The stereochemistry for H-8 and H-9 was determined from the NOESY spectrum, which showed cross-peaks between H-7/H-8, H-7/H-9, H-8/H-13 and H-9/H-13, suggesting that H-8 is axial and H-9 is equatorial, respectively. The locations of the ester groups were also identified by the HMBC cross-peaks between H-8 and the benzoate carbonyl signal at d 165.3, H-9 and the (3-)furancarboxylate carbonyl at d 161.9, the H-13 and the acetate carbonyl at d 170.4, and H-1 and H-6 between 2-methylbutanoate carbonyl groups at d 174.5 and 175.1, respectively.…”
mentioning
confidence: 99%
“…In skeleton of β-dihydroagarofuran sesquiterpene, H-1 and H-6 have axial stereochemistry. 5,6 From the results of the NOESY spectrum of 1, the correlation between H-6 and H-9 indicated the presence of H-9eq (Fig. 1).…”
mentioning
confidence: 96%